A heuristic algorithm for the university course timetabling problems by considering measure index: a case study. (1st January 2014) - Kaviani, Mohadese; Shirouyehzad, Hadi; Sajadi, Seyyed Mojtaba; Salehi, Mohammadreza
University timetabling problems, particularly the timetables of courses and examinations are among the most difficult tasks which educational institutions are faced with. Manual solution of a university timetabling problem requires a great domain of time and resources. As generating an operable and applicable programme with the least overlapping in the teachers' schedules and overlapping in the curriculum is not easy, various mathematical models and algorithms are proposed to solve such problems. But any of these strategies have considered different limitations due to their operating media and environment. This paper proposed a heuristic algorithm for university course timetabling problem. In the proposed algorithm, as the operations and steps are random or stochastic, it is not possible to provide a united and unique timetable. Then after providing such a timetable the best solution is chosen among the generated ones through measure index. The proposed algorithm was tested with real data from Najaf Abad Islamic Azad University, the departments of industrial engineering higher education and MA degree in the semester of 2012–2013. The results reveal that the applied approach is able to generate a timetable which can satisfy the purposes of interest.